Metabolomics analysis of the effect of GnRH on the pregnancy rate of ewes with estrus synchronization scheme based on progesterone - Zhang, Jing; Sun, Shuyuan; Bai, Xinyu; Yang, Nana; Liu, Yiyong; Wu, Xinglong; Li, Xiangyun (Frontiers in Veterinary Science, 2024)
Introduction Gonadotropin-releasing hormone (GnRH) is widely used in the timed artificial insemination protocol for sheep. However, there remains a debate regarding its impact on pregnancy rates during artificial insemination. This study aims to evaluate the effect of GnRH on the pregnancy rates in Huyang ewes, analyze the pre-implantation metabolite changes caused by GnRH using metabolomics, and elucidate the mechanism effect on pregnancy rates. Methods All ewes were administered a vaginal progesterone sponge containing 45 mg of flurogestone acetate for 12 days and received 330 units of equine chorionic gonadotropin (eCG) intramuscularly after sponge removal. The experimental group (n = 69) received an intramuscular treatment of 17 μg GnRH agonist triptorelin 48 h after sponge removal on Day 0, while the control group (n = 41) received 1 mL of sterile saline solution. All ewes underwent a single vaginal insemination 58 h after the withdrawal of the progesterone sponge. The difference in pregnancy rates between the two groups was calculated. Metabolomic analysis was performed on plasma samples collected on Day 7 after the treatment of GnRH agonist. Results Gonadotropin-releasing hormone (GnRH) treatment significantly reduced the pregnancy rate in the experimental group compared with the control group (72.2 vs. 82.9%, p < 0.05). Metabolomic analysis indicated that GnRH treatment affected metabolites involved in collagen synthesis and prostaglandin synthesis in the endometrial tissue, which includes a marked decrease in hydroxyproline amino acid content and a significant increase in corticosterone and prostaglandin D2 lipids and unsaturated fatty acids. Conclusion In summary, the injection of GnRH agonist Triptorelin 48 h after progesterone sponges removal reduces the pregnancy rate of Huyang ewe following artificial insemination. It also affects the metabolite levels related to endometrial collagen and prostaglandin synthesis, harming embryo implantation.